An overview on cooling led lamps - Lê , Bá Tân; Đặng , Thành Trung (Journal of Technical Education Science, 2013)
Nowadays, using light emitting diode (LED) in industry has become more popular not only it needs low consumption in electricity, but also it can provide high luminosity. The efficiency of using LEDs is higher than other conventional lamps because of two these following reasons: - Using LEDS require less electric energy than incandescent and fluorescent bulbs; however, they still supply more lighting capability per watt than incandescent and fluorescent bulbs. - Because they require low electric energy, so it is friendly with our environment. However, it is estimated that approximately 70-85% LED power is converted into heat energy; the higher LEDs power, the more generated heat. The high working temperature would reduce the LED lifetime and brightness. Therefore, it is nessesary to dissipate heat from LED lamps. This paper has reviewed the newest approaching research for this issue.